Assessment of the effectiveness of computer assisted teaching programme on knowledge regarding menstrual blood banking among B.Sc. nursing students at SRM College of Nursing, Kattankulathur, Chengalpet District - P., Abirami (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Stem cells in menstrual blood have regenerative capabilities as the stem cells in umbilical cord blood and bone marrow. Cryo – cell patent – pending menstrual stem cells service offers women in their reproductive years the ability to store and preserve these cells for potential controversy. Cryo–cell is the only bank in the world that can offer women the reassurance and peace of mind that comes with the opportunity. The objective of the study was to determine the effectiveness of computer assisted teaching programme on knowledge regarding menstrual blood banking among BSc Nursing students in study group. Method: The research approach was Quantitative approach. The research design adopted for the study was quasi experimental research design. The sample size was 302 BSc Nursing students in which 151 in study group and 151 in control group. The samples were selected by non-probability convenient sampling technique at SRM College of Nursing, Kattankulathur 30 samples per day were selected and conducted pretest on the same day, Computer assisted teaching were provided on menstrual blood banking for 15 minutes and post test was conducted on 7th day. The data was collected from the sample were tabulated and analysed and interpreted using both descriptive and inferential statistical method. Result: The p value is less than 0.01 and is highly significant at 1% level. Conclusion: Therefore, we can conclude that the knowledge level was increased in study group due to computer assisted teaching programme and it was effective in improving the knowledge of BSc Nursing students regarding menstrual blood banking.